"Wearing a Mask Won't Protect Us from Our History": The Impact of COVID‐19 on Black Children and Families. Issue 2 (18th July 2022) - Bogan, Erin; Adams‐Bass, Valerie N.; Francis, Lori A.; Gaylord‐Harden, Noni K.; Seaton, Eleanor K.; Scott, Judith C.; Williams, Joanna L.
ABSTRACT: The data on COVID‐19 show an irrefutable and disturbing pattern: Black Americans are contracting and dying from COVID‐19 at rates that far exceed other racial and ethnic groups. Due to historical and current iterations of racism, Black Americans have been forced into conditions that elevate their risk for COVID‐19 and consequently place Black children at the epicenter of loss across multiple domains of life. The current paper highlights the impact of the pandemic on Black children at the individual, family, and school levels. Based on an understanding of the influence of structural racism on COVID‐19 disparities, policy recommendations are provided that focus on equitable access to quality education, home ownership, and employment to fully address the needs of Black children and families during and after the pandemic. Research, practice, and policy recommendations are made to journal editors, funding agencies, grant review panels, and researchers regarding how research on COVID‐19 should be framed to inform intervention efforts aimed at improving the situation of Black children and families.